PELAKSANAAN PROGRAM PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) DI SD NEGERI 006 PALEMBANG - Dewi Kartika Sari; Ihsan Hafizh; Melianita Margativera; Adelia Safitri; Ayu Indriyati; Azzahra Junita Hendra; Ayu Agustina; Alifia Dea Husanah; Imelia Nur Zahara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The School Field Introduction Program (Pengenalan Lapangan Persekolahan/PLP) is an academic program designed to provide prospective teachers with direct experience in the school environment. This study aimed to describe the implementation of the School Field Introduction Program conducted by students of Universitas PGRI Palembang at SD Negeri 006 Palembang and to identify its benefits, supporting factors, and challenges encountered during the program. This research employed a qualitative approach using a descriptive method. Data were collected through observations, documentation, and field notes during the implementation of the PLP program from March 2 to May 13, 2026. The findings revealed that the program was carried out through several stages, including school observation, classroom observation, teaching assistance, and independent teaching practice. The program provided students with direct experience in understanding the school environment, student characteristics, learning processes, and teachers’ professional responsibilities. Furthermore, the PLP program contributed significantly to the development of students’ pedagogical, professional, social, and personal competencies. Supporting factors included guidance from mentor teachers and university supervisors, a conducive school environment, and support from the school community. The challenges encountered included diverse student characteristics, limited student concentration during certain learning periods, and classroom management difficulties. Overall, the School Field Introduction Program at SD Negeri 006 Palembang was successfully implemented and effectively enhanced the readiness of Universitas PGRI Palembang students to become professional educators.